The Istituto Mosso LTER site (Aosta Valley, Italy): an integrated research - monitoring in an alpine permafrost area. Site instrumentation and techniques - COLOMBO, NICOLA; FRATIANNI, SIMONA; GUENZI, DIEGO; ACQUAOTTA, FIORELLA; GIARDINO, Marco; PEROTTI, Luigi; FREPPAZ, Michele; GODONE, DANILO FRANCESCO; SAID PULLICINO, DANIEL; ISAIA, MARCO; E. Giaccone; G. Viviano; et al. (S. Perona, S. Casale, 2014)
Rock glaciers are the most prominent geomorphic features related to the presence of permafrost in mountain areas. Climate warming is likely to have strong impacts on permafrost status, making cold areas at high altitudes especially vulnerable. Therefore, climate evolution and its impact on abiotic and biotic components of permafrost environments is a research topic of increasing importance. In this work the active Col d’Olen rock glacier, located in the Istituto Mosso LTER (Long Term Ecological Research) site, in the Aosta Valley Region (NW-Italian Alps), is the object of an interdisciplinary investigation. Instrumentation and techniques are described below. Climatic data from automatic weather stations have been collected in the study area and they will be updated and analysed. Moreover, a network of portable instruments will be established (during the summer 2014) on the rock glacier for collecting meteorological data, after a dedicated calibration procedures to assess the uncertainties of the measures, in the framework of MeteoMet2 project. The physical and chemical characteristics of the rock glacier outflow are under investigation by using temperature dataloggers and a multi-parametric probe spectro::lyserTM (NO3-N and DOC). Regular sampling of water on weekly basis has been also established for investigating major ion concentrations (e.g. Ca2+, Mg2+, etc.), trace elements (e.g. Ni, Si, etc.) and isotopic analyses (δ18O). Moreover, the chemical characteristics of snow and fine-grained material are under analysis. The ground surface temperature monitoring will be conducted using Maxim iButton® DS1922L mini-thermocrons and Hobo TidbiTv2 temperature loggers, regularly distributed on the rock glacier’s surface and in a few selected surrounding sites. Total station and differential GNSS instruments will allow an accurate grid distribution and to acquire the coordinates of the dataloggers. In addition, high resolution digital terrain models (DTM’s) and thermal images of the rock glacier area will be obtained from ...